FIRM SIZE SEBAGAI PEMODERASI PROFITABILITAS DAN LIKUIDITAS PADA NILAI PERUSAHAAN - Putu Pande R. Aprilyani Dewi (JURNAL AKUNTANSI, 2023)
This study determines the effect of the profitability and liquidity on firm value. The population of this study is composed of mining companies listed on the Indonesian Stock Exchange from 2018 to 2021. The study used a purposive sampling technique and obtained a sample of 56 companies. The results of this study indicate that profitability and liquidity effect the value of mining companies listed on the Indonesian Stock Exchange. Firm size strengthens the influence of profitabilitas on the value of mining companies, this is because large companies can more easily obtain external funds in the form of large amounts of debt that can help a company’s operational activities. Firm size strengthens the influence of liquidity on the value of mining companies, this is because firm size becomes a measure that can describe the size of the company, where with the existence of liquidity and firm value at company size if it does not meet the liquidity value then the company value is not good.